1994
DOI: 10.1002/polb.1994.090321306
|View full text |Cite
|
Sign up to set email alerts
|

Ostwald ripening in an immiscible hydrogenated polybutadiene and high‐density polyethylene blend

Abstract: The long‐time regime coarsening in a phase‐segregated blend of hydrogenated polybutadiene (HPB) with high‐density polyethylene (HDPE) was studied. The blend consisted of 10 wt% of HPB in a HDPE matrix. The morphology of the system was studied by etching the HPB particles from the HDPE matrix and observing the etched specimens in a scanning electron microscope. The average volume of the HPB particles was found to increase with storage time in the melt, and to follow a temporal exponent of 1 in agreement with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 28 publications
3
32
0
Order By: Relevance
“…If the EPR copolymer behaves like a surfactant reducing the interfacial tension and stabilizing ripening). [37][38][39] Quantifying the contribution of each process here is difficult. The larger domains the system, two major effects should be detectable in a PE/EPR/PP blend: a slowing down of the of the PE phase formed are not spherical, and coarsening rate and the formation of a finer disratio, and examine the effects of the copolymer on the morphology of the system.…”
Section: Resultsmentioning
confidence: 99%
“…If the EPR copolymer behaves like a surfactant reducing the interfacial tension and stabilizing ripening). [37][38][39] Quantifying the contribution of each process here is difficult. The larger domains the system, two major effects should be detectable in a PE/EPR/PP blend: a slowing down of the of the PE phase formed are not spherical, and coarsening rate and the formation of a finer disratio, and examine the effects of the copolymer on the morphology of the system.…”
Section: Resultsmentioning
confidence: 99%
“…In these cases, the rate equation (4.4) generally holds. Furthermore, LSW theory is used to describe size changes in polymer mixtures (poly butadiene particles in polyethylene [393]) or for the growth of gas bubbles in metals (10 nm helium bubbles in precious steel [394]) . Furthermore, LSW theory is used to describe size changes in polymer mixtures (poly butadiene particles in polyethylene [393]) or for the growth of gas bubbles in metals (10 nm helium bubbles in precious steel [394]) .…”
Section: Atomic Diffusion and Ostwald Ripeningmentioning
confidence: 99%
“…This finding has led to the general acceptance of the Lifshitz–Slyozov–Wagner (LSW) model for the time dependence of the average particle radius:11 where the value of K varies with the ripening mechanism 9. Both experiments1, 2 and numerical simulations15 based on the Cahn–Hilliard theory have shown that the coarsening process follows eq 2 in binary systems. In addition, the nonlinear diffusion model is capable of predicting both Ostwald ripening and particle coalescence.…”
Section: Introductionmentioning
confidence: 99%
“…The coarsening of particles in a phase‐separated polymer blend has received much attention in the recent literature 1–9. This is due in part to the importance of particle size with respect to the physical properties of a given blend.…”
Section: Introductionmentioning
confidence: 99%